Hollow Copper Sulfide Nanoparticle-Mediated Transdermal Drug Delivery - Ramadan, Samy (2012)
Nanoparticles with strong optical absorption at near-infrared (NIR) wavelengths can efficiently convert optical energy into thermal energy, and have shown multimodality in biological and biomedical applications. In this work, a new type of thermal ablation-enhanced transdermal delivery methodology is developed based on hollow copper sulfide nanoparticles (HCuSNPs) with intense photothermal coupling effects. Application of nanosecond-pulsed NIR laser allows rapid heating of the nanoparticles and instantaneous heat conduction. This provides very short periods of time but extremely high temperatures (estimated over 100°C) in local regions, with focused thermal ablation of the stratum corneum. Because the discontinuous light from the pulsed laser minimized heat accumulation, the average temperature of the irradiated skin area only increases to ~40–50°C. The extent of thermal ablation of skin, i.e. removal of the stratum corneum, viable epidermis, or the dermis, can be controlled by adjusting the laser power. The skin disruption by HCuSNP-mediated photothermal ablation significantly increases the permeability of macromolecule drugs such as human growth hormone, providing effective and controlled percutaneous delivery. This technique offers compelling opportunities to overcome low oral bioavailability of small- and large-molecular-weight drugs, avoiding the pain and inconvenience of long-term s.c. injections while enabling sustained and controlled delivery.